The impact of remuneration and recognition on lecturers’ workload: an approach to work engagement - Rosita, Sry; Fazri, Andang; Musnaini, Musnaini; Mala Fithriani Aira, Dian (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The purpose of the research is to examines the remuneration and recognition in influencing work engagement to increase lecturers’ workload. The research design used survey research with quantitative research. Sources of data in this study using a structured questionnaire. The target population in this study were lecturers who received remuneration (PNS) at Jambi University, the research sample amounted to 89 lecturers. The software used is smart-PLS. The results showed that remuneration has no effect to the lecturer's workload, recognition has an effect to the lecturer's workload, remuneration has no effect to work engagement, remuneration has no effect to work engagement in improving lecturer’s workload, recognition has an effect to lecturer’s work engagement, work engagement has an effect to the lecturer's workload, recognition has an effect to work engagement in improving lecturer’s workload. The remuneration has no effect to work engagement in improving lecturer’s workload, it is necessary to practice strong management in implementing remuneration so that it can be perceived as well as recognition which is able to create prosperity and strong attachment in carrying out their duties as a lecturer.